2016
DOI: 10.1097/j.pain.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Increased cutaneous miR-let-7d expression correlates with small nerve fiber pathology in patients with fibromyalgia syndrome

Abstract: Fibromyalgia syndrome (FMS) is a chronic widespread pain condition probably comprising subgroups with different underlying pathomechanisms. There is increasing evidence for small nerve fiber impairment in subgroups of patients with FMS. MicroRNAs (miRNAs) regulate molecular factors determining nerve de- and re-generation. We investigated whether systemic and cutaneous miRNA expression in patients with FMS is related to small nerve fiber pathology. We confirmed previous findings of disturbed small fiber functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 85 publications
3
58
0
Order By: Relevance
“…Absent LEPs and SSR may also underlie a small fibers involvement with clinical appearance of neuropathic features, as assessed by DN4 test. As far as evidence is increasing in respect to central and peripheral nervous involvement in FM [53], the present results could point out the opportunity to submit such patients to the neurophysiological assessment of nociceptive and vegetative systems, possibly completed by skin biopsy.…”
Section: Discussionmentioning
confidence: 83%
“…Absent LEPs and SSR may also underlie a small fibers involvement with clinical appearance of neuropathic features, as assessed by DN4 test. As far as evidence is increasing in respect to central and peripheral nervous involvement in FM [53], the present results could point out the opportunity to submit such patients to the neurophysiological assessment of nociceptive and vegetative systems, possibly completed by skin biopsy.…”
Section: Discussionmentioning
confidence: 83%
“…In recent studies, small nerve fiber pathology was found in subgroups of patients with fibromyalgia syndrome (FMS) . Applying corneal confocal microscopy (CCM), corneal denervation was also reported in FMS patients …”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have found heat related hypoesthesia and hypoalgesia in patients with lateral epicondylalgia 34 increased thermal detection thresholds, and skin biopsies confirmed a loss of small thin cutaneous never fibers. Leinders et al, 2016 37 recently found that several systemic mirco-RNAs (miR), specifically miR-103, miR-151, and miR-let-7d, were downregulated in patients with fibromyalgia whereas cutaneous miR-let-7d was elevated in patients with reduced small nerve fiber density. miR-let7d has previously been found to be associated with chronic pain in patients with complex regional pain syndrome 38 and to affect the endogenous opioid system 39 , which is known to be impaired in, e.g.…”
Section: Thermal Testing In Knee Osteoarthritismentioning
confidence: 99%